2023
DOI: 10.1080/07853890.2023.2191218
|View full text |Cite
|
Sign up to set email alerts
|

The melatonin receptor 1B gene links circadian rhythms and type 2 diabetes mellitus: an evolutionary story

Abstract: Disturbed circadian rhythms have been a risk factor for type 2 diabetes mellitus (T2DM). Melatonin is the major chronobiotic hormone regulating both circadian rhythm and glucose homeostasis. The rs10830963 (G allele) of the melatonin receptor 1B ( MTNR1B ) gene has the strongest genetic associations with T2DM according to several genome-wide association studies. The MTNR1B rs10830963 G allele is also associated with disturbed circadian phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 232 publications
(213 reference statements)
0
13
0
1
Order By: Relevance
“…Associations between the carriage of the MTNR1B rs10830963 minor G-allele and the affected modulation of the metabolic response to melatonin and light were evident in previous studies [42][43][44]. Carriers of the minor G-allele of the MTNR1B rs10830963 snp represent a large part of populations that have elevated fasting glucose and higher risks of metabolic disorders, particularly type 2 diabetes mellitus [41]. They also have changed and prolonged patterns of melatonin secretion [42] that can be related to chronotype [43] or reduced light signaling due to retinal ganglion cell loss [44].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Associations between the carriage of the MTNR1B rs10830963 minor G-allele and the affected modulation of the metabolic response to melatonin and light were evident in previous studies [42][43][44]. Carriers of the minor G-allele of the MTNR1B rs10830963 snp represent a large part of populations that have elevated fasting glucose and higher risks of metabolic disorders, particularly type 2 diabetes mellitus [41]. They also have changed and prolonged patterns of melatonin secretion [42] that can be related to chronotype [43] or reduced light signaling due to retinal ganglion cell loss [44].…”
Section: Introductionmentioning
confidence: 75%
“…This SNP is associated with disrupted circadian phenotypes and also with altered melatonin secretion [42][43][44]. Both factors are prerequisites for metabolic disturbances and diabetes [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study revealed that individuals with prediabetes and insulin resistance exhibit lower excretion levels of melatonin metabolites in their urine (6-sulfatoxymelatonin) [ 16 ]. Numerous studies have also investigated the relationship between polymorphisms in the gene responsible for expressing melatonin MTNR1B receptors and elevated susceptibility to developing type 2 diabetes mellitus (T2DM) and circadian disorders [ 17 , 18 ]. Melatonin is a hormone that signals the circadian rhythm.…”
Section: Introductionmentioning
confidence: 99%